2001
DOI: 10.1177/016235320102400302
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Social Characteristics of Boys with AD/HD and Giftedness: A Comparative Case Study

Abstract: The purpose of this multiple case study was to investigate the emotional and social characteristics of boys who had co-occurring giftedness and AD/HD as compared with boys with only 1 of the 2 exceptionalities. The participants were 3 boys with AD/HD and giftedness and 6 comparison boys with only 1 of the 2 exceptionalities. Data sources included the participating boys, their parents, and their teachers. Data were collected by a team of researchers using parallel forms of a semistructured interview protocol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 69 publications
(92 reference statements)
0
41
0
5
Order By: Relevance
“…We categorized these articles as multiple categories. For instance, in a study of gifted males with attention deficity hyperactivity disorder (ADHD; Moon, Zentall, Grskovic, Hall, & Stormont, 2001), qualitative case-study methods were used in addition to descriptive methodology pertaining to survey data from the subjects. Because this article was both qualitative and descriptive, we labeled it as multiple categories.…”
Section: Article Classificationmentioning
confidence: 99%
“…We categorized these articles as multiple categories. For instance, in a study of gifted males with attention deficity hyperactivity disorder (ADHD; Moon, Zentall, Grskovic, Hall, & Stormont, 2001), qualitative case-study methods were used in addition to descriptive methodology pertaining to survey data from the subjects. Because this article was both qualitative and descriptive, we labeled it as multiple categories.…”
Section: Article Classificationmentioning
confidence: 99%
“…One recent study that looked at boys with both the gifted and ADHD labels found that giftedness did not seem to be a protective factor for these boys. There is some preliminary data that disabilities such as ADD or ADHD overpower the giftedness of the child (Moon, Zentall, Grskovic, Hall, & Stormont, 2001). From the parents' perspective, their children were receiving services that addressed their challenges, primarily their special education label, rather than their strengths.…”
Section: Dual Exceptionalitiesmentioning
confidence: 99%
“…12 Research has shown that gifted students with ADHD characteristics have higher levels of creativity than gifted students without ADHD characteristics. 13,14 Building on these findings, additional research has indicated that non-gifted individuals with ADHD perform higher on specific areas of creativity than non-gifted individuals. 6,15,16 Not only does research support the idea that those with ADHD score higher on creativity assessments, but also a study examining the real world creative achievement among adults with ADHD found that "adults with ADHD showed higher levels of original creative thinking and higher levels of real-world creative achievement when compared to adults without ADHD".…”
Section: Creative Potential Of Individuals With Adhd Characteristicsmentioning
confidence: 99%
“…2 Published literature supports the idea that individuals with ADHD may have the potential to be more creative than their peers. [3][4][5][6][7] Their ability to be spontaneous and divergent thinkers allows them to take more risks. As they naturally tend to think outside of the box, individuals with ADHD have the potential to offer unexpected solutions to complex problems.…”
Section: Introductionmentioning
confidence: 99%